IMPROVING LECTURER PERFORMANCE THROUGH STRENGTHENING TRANSFORMATIONAL LEADERSHIP, WORK MOTIVATION, AND JOB SATISFACTION: Path Analysis and SITOREM Study on Lecturers at Universitas Panca Sakti Bekasi - Fitrah Mulyanti; Prof. Dr. Sri Setyaningsih; Dr. Griet Helena Laihad (SUJANA: Education and Learning Review, 2024)
This research aims to find strategies, ways and optimal solutions to improve lecturer performance by analyzing the impact of transformational leadership, motivation and job satisfaction on lecturer performance. This research uses a survey method with a path analysis approach with further SITOREM analysis. This research discusses that to improve lecturer performance, we need to focus on three factors: transformational leadership, work motivation, and job satisfaction. The variable analysis indicates that transformational leadership has a direct impact on lecturer performance, by improving transformational leadership will strengthen lecturer performance. Furthermore, work motivation and job satisfaction also have a direct impact on lecturer performance. Transformational leadership and work motivation also have an impact on job satisfaction, which then affects lecturer performance indirectly. Therefore, strengthening these aspects can help improve lecturer performance through increased job satisfaction. The results of the SITOREM analysis indicate that there are 11 things that need to be improved, such as salary/wages, supervision, Tridharma Perguruan Tinggi, delegation of authority, opportunities for achievement, desire to work, work goals, good work environment, quality and quantity of work, and efficiency. On the other hand, there are 6 other things that can be improved, such as promotion opportunities, support from coworkers, encouraging motivation, intellectual stimulation, appreciation from the environment, and work effectiveness.